Implications for Savings of Aging in the Asian 'Tigers' - Symansky, Steven (IMF Working Papers; Working Paper, 1997)
Significant aging is projected for many high-saving emerging economies of East and Southeast Asia. By 2025, the share of the elderly in their populations will at least double in most of these countries. The share of the young will fall. Aging populations could adversely affect saving rates in these economies, particularly after 2025. For the world, one may observe that, initially, the Asian Tigers could become increasingly important for world savings, reflecting their increased weight in the world economy, their high saving and growth rates, and the aging of the industrial countries. After 2025, the aging of the Tigers may reinforce the tendency toward a declining world saving rate.